Serous Cystic Tumor of the Pancreas: Are There Indications to Operate? - Monari, Francesco; Ricci, Claudio; Taffurelli, Giovanni; Ingaldi, Carlo; Pezzilli, Raffaele; Santini, Donatella; D'Ambra, Marielda; Buscemi, Salvatore; Lazzarini, Enrico; Calculli, Lucia; Zingaretti, Caterina Costanza; Pacilio, Carlo Alberto; et al. (JOP. Journal of the Pancreas, 2013)
Context Serous cystic tumours (SCTs) of the pancreas are regarded as a benign entity with rare malignant potential. Surgical resection is generally considered curative. It was usually performed in large, symptomatic tumours or in cases in which the diagnosis was not clear. Objective To evaluate factors related to the surgical indication. Methods From 2000 to 2013, data of 43 patients affected by SCTs were collected in a prospective database. Demographics, clinical, radiological, surgical and pathological data were considered as factors related to surgical indication. After 2000 all patients were observed by a dedicated team including radiologists, surgeons, gastroenterologists and pathologists. Thus, patients were divided in two periods, before and after the 2000, to assess if there had been difference over the time in the management of this type of tumours. Univariate and multivariate analysis were performed. Results Thirty-three patients (76.7%) underwent surgical resection, while 10 (23.3%) entered in a surveillance program. At univariate analysis, factors related to surgery were: symptoms (P=0.026), radiological presence of microcysts of diameter <1 mm (P=0.020) and radiological diagnosis different from a SCTs (P=0.018). The multivariate analysis confirmed that symptoms increased the risk of surgery (OR=34.0; 95% CI: 2.1-545.1; P=0.013). The period in which the patients were enrolled, before and after 2000, did not influence the indication to surgery. Conclusions In our experience the only factor related to surgery was the presence of symptoms.